Molecular characterization workflow of gene-edited rice lines: from development to securing non-transgenic status - Guevarra, Precious; Arcillas, Erwin; Matres, Jerlie Mhay; Enriquez, Blesilda; Kohli, Ajay; Slamet-Loedin, Inez; Trijatmiko, Kurniawan Rudi (International Rice Research Institute, 2024)
Genome editing technology enables precise, cost-effective, and rapid introduction of desirable traits to crops overcoming the limitations posed by conventional plant breeding and transgenesis. Ensuring the presence of desired edits, verifying the editing system's accuracy, and securing non-transgenic status are all crucial in expediting development, Philippine regulatory compliance, and the eventual deployment of plants generated through genome editing. This work outlines a streamlined molecular characterization workflow for gene-edited rice lines, covering the entire development process from construct design to achieving non-transgenic state as a requirement for the certificate of non-coverage from the DOST-DA-DENR-DOH-DILG Joint Department Circular No. 1, Series of 2021 (JDC No.1, s. 2021).